2023
DOI: 10.3390/ijerph20032023
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Job Satisfaction and Depressive Symptoms among Chinese Adults Aged 35–60 Years: The Mediating Role of Subjective Well-Being and Life Satisfaction

Abstract: The purpose of this study was to assess the serial multiple mediating effects of subjective well-being and life satisfaction between job satisfaction and depressive symptoms among Chinese adults aged 35–60 years. According to the 2018 China Family Panel Study (CFPS), we finally selected 10,609 respondents (5202 females, and 5407 males) aged 35–60 years old as samples for the study. Correlation analysis was carried out to examine the relationship among job satisfaction, subjective well-being, life satisfaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Previous research found that life satisfaction, particularly JS [63], is associated with a range of long-term work-life conflicts [69,70]. Compared to other types of life dissatisfaction, job dissatisfaction is known to have a stronger association with depressive symptoms [56].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research found that life satisfaction, particularly JS [63], is associated with a range of long-term work-life conflicts [69,70]. Compared to other types of life dissatisfaction, job dissatisfaction is known to have a stronger association with depressive symptoms [56].…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has established that JS encompasses six dimensions: job income, work environment, job security, working hours, career development and overall job experience [61][62][63]. As part of the CFPS, participants were required to respond using a five-point Likert scale as extremely dissatisfied, dissatisfied, neutral, satisfied and extremely satisfied; this 5point scoring method sums the scores for all six dimensions into a scale with a score ranging from 6-30.…”
Section: Job Satisfaction (Js)mentioning
confidence: 99%
“…Our study also showed that contract nurses were more likely to experience depressive symptoms compare to the formal employee. Due to the inequitable benefit structures of nurses, contract nurses have a lower level of job satisfaction [ 45 ], which can cause them to experience depressive symptoms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ez az eredmény összhangban van Liu, Y. és munkatársai keresztmetszeti N=10609, 35-60 év közötti kínai munkavállaló körében végzett vizsgálati eredményeivel is, mely szerint a munkahelyi elégedettség indirekt hatást gyakorol a depressziós tünetegyüttesre, melyet a szubjektív jóllét és az élettel való elégedettség tényezőinek sorozatos mediáló hatásán keresztül fejti ki. Az eredmények alapján a munkahelyi elégedettség növelése csökkentheti a depressziós tüneteket a szubjektív jóllét és az élettel való elégedettség előmozdításán keresztül [21]. Továbbá eredményeink szerint a depressziós tünetegyüttes kialakulásának kockázatát a modellen belül a Munka-család konfliktus (Wald=1006; OR=2,27) mint rizikófaktor szignifikánsan növelheti.…”
Section: A Depressziós Tünetegyüttes Főbb Pszichoszociális Kockázati ...unclassified